EVALUATION OF THE ANTI-EXUDATIVE EFFECT OF OINTMENT WITH ONONIS SPINOSA L. EXTRACT IN MODELS OF INFLAMMATION OF VARIOUS ORIGIN - Nefodov, O.O.; Eberle, L.V.; Ustyanska, O.V.; Tsisak, A.O.; Alexandrova, O.I.; Radaeva, I.M.; Ostapchuk, K.V. (World of Medicine and Biology, 2025)
Experimental studies on the antiexudative activity of Ononis spinosa L. extract were conducted in models of trypsin and zymosan-induced inflammation. To assess the activity of the plant extract, ointments of varying concentrations (1.5 %, 2.5 %, 3.5 %) in terms of polyphenolic compounds were prepared for transdermal application. According to the study’s results, the 3.5 % ointment exhibited the most pronounced anti-exudative effect, effectively suppressing the focus of inflammation and contributing to an accelerated reduction in the morphological indicators of the affected limbs in rats. The ointment with Ononis spinosa L. extract did not differ significantly, but was not inferior in effect to the comparison drug - Dolgit cream. The obtained data indicate the feasibility of using Ononis spinosa L. extract in the treatment of inflammatory processes, particularly those of infectious origin. The identified pharmacological activity justifies the need for further preclinical and clinical studies. The results obtained may serve as the basis for the development of effective local anti-inflammatory agents of plant origin.